Bhagavadgītā ane arvācīna jīvana Gītāno amara sandeśa : Bhagavad Gita and modern life no adhikr̥ta anuvāda - Munshi, Kanaiyalal Maneklal, 1887-1971 (Śrī Munaśī hīrakamahotsava granthāvali, 1950)
Interpretation of the Bhagavadgītā and life style.